The Effect of Online Learning on Students' Learning Achievement in Class XI IPS SMA N 2 Lubuk Basung, Agam Regency - Milenia, Rika Yulia (Lembaga Riset Mutiara Akbar, 2022)
This research is motivated by the influence of online learning on student achievement and a decrease in student learning achievement. The purpose of this study is to describe: 1) Knowing online learning in class XI IPS at SMAN 2 Lubuk Basung, 2) Knowing online learning achievement in class XI IPS at SMAN 2 Lubuk Basung, 3) Knowing the effect of online learning on student achievement in class XI IPS SMAN 2 Lubuk Basung. This research is a quantitative descriptive research, namely field research. The approach taken is a quantitative approach by studying research problems based on facts that occur and having close relationships with people to obtain research results. In this study, data collection was carried out using observation, questionnaires and documentation and analysis used is linear regression. The population of this research is all 151 class XI students of SMAN 2 Lubuk Basung. The sampling technique used random sampling technique as many as 62 people. The instrument used is a questionnaire. Data analysis using percentage technique